2018
DOI: 10.1038/s41416-018-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of WBP2 with ERα increases doxorubicin resistance of breast cancer cells by modulating MDR1 transcription

Abstract: Our finding provides a new mechanism for the chemotherapy response of ERα-positive breast tumours, and WBP2 might be a key molecule for developing new therapeutic strategies to treat chemoresistance in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…The work by Chen et al implicates WBP2 in the resistance of MCF-7 cells to doxorubicin. Overexpression of WBP2 promoted its interaction with ER, which in turn enhanced ER-mediated transcription of multidrug resistance gene (MDR1) [84].…”
Section: Translational and Clinical Significance Of Wbp2mentioning
confidence: 99%
“…The work by Chen et al implicates WBP2 in the resistance of MCF-7 cells to doxorubicin. Overexpression of WBP2 promoted its interaction with ER, which in turn enhanced ER-mediated transcription of multidrug resistance gene (MDR1) [84].…”
Section: Translational and Clinical Significance Of Wbp2mentioning
confidence: 99%
“…Chemotherapy is a commonly used strategy for treatment of breast cancer. But severe systemic side effects and drug resistance are frequent problems during chemotherapy (Barry, Alvarez, Scully, Miller, & Lipshultz, ; S. Chen et al, ). Therefore, it is necessary to explore and develop novel and effective anti‐breast cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance in cancer cells was associated with the EMT and upregulation of ABC transporters could be an evolutionarily conserved system. The overexpression of MDR1 could be conducive to both initiation and acceleration of the chemotherapy resistance in breast cancer cells [41]. Saxena M. et al suggested that chemotherapeutic drug-induced EMT increased the expression of ABC transporters and induced both the drug resistance and the invasion in breast cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%